Tailor-made 3D in vitro maturation of early antral follicles uncovers cumulus-cell transcriptomic driver signature to predict oocyte competence - Rojo-Fleming, Camila; Konstantinidou, Fani; Peserico, Alessia; Di Berardino, Chiara; Capacchietti, Giulia; Nardinocchi, Delia; Camerano Spelta Rapini, Chiara; Russo, Valentina; Bernabò, Nicola; Capalbo, Antonio; Stuppia, Liborio; Gatta, Valentina; et al. (Frontiers in Endocrinology, 2025)
BackgroundAssisted reproductive technologies (ART) are constrained by the limited pool of medium antral follicles. Early antral follicles (EAfs) are an emerging additional source coming either from cryopreserved ovaries or from in vitro folliculogenesis protocols. The EAfs have the advantage of being gonadotropin sensitive follicles enclosing fully grown oocytes that can be enrolled in ART using advanced IVM techniques. The present research has been designed using the validated 3-D follicle-enclosed IVM protocol to insight into EAfs ART competence by profiling the transcriptome of the surrounding cumulus cells (CCs) to uncover non-invasive predictors of oocyte developmental competence.ResultsTranscriptome analysis of 22–141 genes revealed 1–386 DEGs in CCs supporting metaphase-II (MII) oocytes and 1–420 in CCs enclosing germinal-vesicle (GV) oocytes. Network modelling pinpointed as signature of competent CCs three down-regulated outliers (EFHD1, HS6ST2, SLC35G1) and two hubs (CDC6, KIF11), while the unsuccessful ones revealed six outliers (HBA1, SLC39A8, ERO1A, TKDP5, CALCRL, ELOVL6) and the hub CASP3. The profile of EAfs enclosing competent oocyte converged towards cumulus expansion and controlled cell-cycle quiescence pathways whereas lipid dysregulation, oxidative stress and apoptosis characterized CC surrounding incompetent oocytes. The endpoint comparison yielded 11 markers, highlighted by SEMA3A up-regulation and IL1A, DDIT4 and VNN1 down-regulation. qPCR confirmed the transcriptome profile of the key genes (HS6ST2, CDC6, ERO1, CASP3 and SEMA3A) while immuno-assays corroborated the differential expression and localization of some related codified driver proteins (HAS2, CASP3 and SEMA3A).ConclusionsCC transcriptomics defines a concise 12-gene driver panel plus 11 endpoint markers that accurately predict the maturation fate of individual EAfs by providing actionable targets and a practical basis for rapid, non-invasive selection of high-quality follicles, with potential to enhance fertility preservation, livestock breeding and clinical ART outcomes. In addition, the analysis point on new gene/protein mediating CCs maturation mechanism is to be considered.